2008
DOI: 10.1111/j.1365-2222.2008.03027.x
|View full text |Cite
|
Sign up to set email alerts
|

Early infection with Trichuris trichiura and allergen skin test reactivity in later childhood

Abstract: Early heavy infections with T. trichiura may protect against the development of allergen skin test reactivity in later childhood. Novel treatments to program immune-regulation in early childhood in a way that mimics the effects of early infections with T. trichiura may offer new strategies for the prevention of allergic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
122
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 32 publications
10
122
0
1
Order By: Relevance
“…This study was conducted in the city of Salvador in northeastern Brazil, which has a population of 2.5 million. The prevalence of wheezing in this city in the past 12 months in school children aged 12 to 13 years was reported to be very high (27.1%) (29). The design of this study has been reported elsewhere (6,13,29).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was conducted in the city of Salvador in northeastern Brazil, which has a population of 2.5 million. The prevalence of wheezing in this city in the past 12 months in school children aged 12 to 13 years was reported to be very high (27.1%) (29). The design of this study has been reported elsewhere (6,13,29).…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to pathogens and their products, and to helminths in particular, has been shown to protect against the development of autoimmune and allergic diseases in experimental animal models (7,8,10,23,25,26,28), and some evidence in support of this has been observed in human populations (3,8,10,23,29,30,31).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…2) However, parasitic helminths do not always suppress clinical allergies and can sometimes worsen allergic symptoms. Regarding the timing of helminth infections, a study in Brazil is especially noteworthy (Rodrigues et al, 2008). In the study, heavy infections with T. trichiura in early childhood were shown to reduce reactivity to allergens in later childhood.…”
Section: Influence Of Helminth Infections On Human Atopic Disordersmentioning
confidence: 99%
“…As described in previous publications, [21][22][23] Social Changes, Asthma and Allergy in Latin America (SCAALA) is a research program conducted in Brazil and Ecuador. The Brazilian component comprised a cohort of 1307 (705 males) unrelated children between 4 and 11 years old.…”
Section: Study Design and Population Characterizationmentioning
confidence: 99%